A review: bioactive compounds of macroalgae and their application as functional beverages. Issue 1 (February 2021) - Widyaswari, S G; Metusalach,; Kasmiati,; Amir, N
Abstract: Macroalgae have the potential of a bioactive compound that can be used as the main ingredient in functional beverages. The content of bioactive compounds in macroalgae such as natural pigments, sulfated polysaccharides, antioxidants have been studied and it is very beneficial for health. Macroalgae, which are used as main ingredient in functional beverage, must be contain bioactive compound that are beneficial for health and also must be free from microbiological and heavy metal contamination. This study aims to determine bioactive compound activity and the potential of macroalgae as the primary raw material in the formulation of functional beverages. Studied on the formulation of functional beverages with macroalgae as raw materials have been carried out in the last few decades. All types of macroalgae have the potential to be used as raw material or main ingredient for functional beverage. The formulation of macroalgae functional beverages with other additives can improve the quality of the final product. The addition of natural scented ingredients and containing bioactive compounds can increase the value of taste and increase the nutritions in functional beverage products.